Design and Construction of a Specialised Biomimetic Robot in Multiple Swimming Gaits. (25th November 2015) - Masoomi, Sayyed Farideddin; Gutschmidt, Stefanie; Gaume, Nicolas; Guillaume, Thomas; Eatwel, Connor; Chen, XiaoQi; Sellier, Mathieu
Efficient cruising, manoeuvrability and noiseless performance of fish robots have been attracting people in various scientific realms. Accordingly, a number of fish robots are designed and fabricated so far. However, the existing robots are only capable of one gait of locomotion. This deficiency is addressed by UC-Ika 2 with multiple gaits of locomotion including cruising and manoeuvring that are inspired from two different fishes. This paper aims at presenting the design and fabrication process of UC-Ika 2. The swimming performance of the robot is tested and compared with its previous version UC-Ika 1.